Significance of Removing Comedonecrosis as an Exclusion Criterion in Mammary Low-Risk Ductal Carcinoma In Situ Managed in an Active Surveillance Clinical Trial: An Extrapolation Study Using Retrospective Cases From a Single Center. Issue 4 (26th March 2021) - Zhan, Haiying; Quinn, Marie; Tian, Wanqing; Yan, Li; Khoury, Thaer
Abstract: Objectives: This study aims to investigate the consequences of comedonecrosis omission as an exclusion criterion of the Comparison of Operative vs Monitoring and Endocrine Therapy (COMET) trial. Methods: The clinical inclusion criteria of the COMET trial were applied on women who were mammographically screened between 2007 and 2017 and had a diagnosis of low- or intermediate-grade ductal carcinoma in situ (DCIS). The percentage of ductal diameter occupied by necrosis was calculated. Results: Twenty-six of 129 (20.2%) cases were upgraded. Larger calcification span correlated with upgrade (P = .02), with the best cutoff of 1.1 cm, and negative predictive value of 86%. When solely analyzing cases with no comedonecrosis (n = 76), none of the variables correlated with upgrade. Comedonecrosis was significantly correlated with upgrade to invasive carcinoma (P = .041), with the best cutoff of 53% of ductal diameter occupied by necrosis. Conclusions: Results indicate that comedonecrosis and span of mammographic calcifications could be risk factors in women managed with active surveillance.